Control the Entire Journey of Pesticide Application on Superhydrophobic Plant Surface by Dynamic Covalent Trimeric Surfactant Coacervation. (13th November 2020) - Liu, Bin; Fan, Yaxun; Li, Haofei; Zhao, Weiwei; Luo, Siqi; Wang, Hua; Guan, Bo; Li, Qiaolian; Yue, Jiling; Dong, Zhichao; Wang, Yilin; Jiang, Lei
Abstract: Vast wastage of pesticides has caused significant environmental pollution and economic loss, which occurs in any step during the entire process of pesticide application. However, the existing strategies for controlling pesticide losses are step specific. Here, a comprehensive strategy to substantively improve pesticide efficiency on the basis of precise designs from beginning to end is developed. A water‐based coacervate with synthesized imine‐based dynamic covalent trimeric surfactants to synergistically control encapsulation, deposition, retention, and release of pesticides on water‐repellent plants is constructed. The coacervate consists of nanosized networks and abundant tightly bonded water, leading to effective encapsulation of hydrophilic/hydrophobic pesticides. Meanwhile, the network‐like microstructure entangles with the micro/nanostructures of superhydrophobic surface, ensuring complete deposition on superhydrophobic plant surface after high‐speed impact and inhibition of wind/rainwater erosion. Moreover, the CO2 ‐induced degradative surfactant coacervate determines the precise pesticide release. The dynamic coacervate as an innovative pesticide formula provides a prospective way for pesticide application, and is expected to promote productive and sustainable agriculture. Abstract : The pesticide encapsulated coacervate fully realizes impact deposition on the super‐hydrophobic leaf surface, excellent anti‐rainwater erosion performance, and controlled release of pesticide, which inhibit pesticide loss and provide a new and feasible strategy for the design of pesticide formulation.